Prevention of Succinylcholine Induced Postoperative Myalgia by Pretreatment with Lignocaine: A Randomized Controlled Study (Faridpur Medical College Journal, 2020)
Succinylcholine, a depolarizing muscle relaxant possesses a unique property of rapid onset and short duration of action, but is accompanied by side effects such as fasciculation and myalgia. The aim of this study was to investigate the prophylactic effect of intravenous lignocaine on the incidence and severity of succinylcholine-induced postoperative myalgia. This was a randomized controlled double blind study conducted at National Institute of ENT Dhaka, during September to December 2017. Eighty adult patients of American Society of Anesthesiologists status I and II of both sexes for elective surgery under general anesthesia were randomly allocated into two equal groups, lignocaine group and normal saline group. The patients of lignocaine group were pretreated with lignocaine 1.5 mg/kg body weight in 5 ml volume, while patients of normal saline group were given isotonic saline 0.9% in the same volume (5 ml) intravenously. Thereafter, anesthesia was induced in all patients, by injecting 1.5 mg/kg of fentanyl and 2 mg/kg of propofol intravenously. Following the loss of eyelid reflex, 1.5 mg/kg of succinylcholine was injected intravenously as a muscle relaxant and then the patients were intubated. The incidence and severity of myalgia were assessed by a blinded observer 24 hours after surgery. In terms of demographic data, the results of this study showed that there is no significant difference between patients in both groups (P>0.05). Overall, the incidence and severity of succinylcholine-induced myalgia in lignocaine group was significantly less, when compared with normal saline group (P